Open Science: Open Data, Open Models, …and Open Publications?. Issue 4 (7th April 2021) - Clark, Martyn P.; Luce, Charles H.; AghaKouchak, Amir; Berghuijs, Wouter; David, Cédric H.; Duan, Qingyun; Ge, Shemin; van Meerveld, Ilja; Zheng, Chunmiao; Parlange, Marc B.; Tyler, Scott W.
Abstract: This commentary explores the challenges and opportunities associated with a possible transition of Water Resources Research to a publication model where all articles are freely available upon publication ("Gold" open access). It provides a review of the status of open access publishing models, a summary of community input, and a path forward for AGU leadership. The decision to convert to open access is framed by a mix of finances and values. On the one hand, the challenge is to define who pays, and how, and what we can do to improve the affordability of publishing. On the other hand, the challenge is to increase the extent to which science is open and accessible. The next steps for the community include an incisive analysis of the financial feasibility of different cost models, and weighing the financial burden for open access against the desire to further advance open science. Key Points: Open science is perhaps the most important paradigm shift in the recent history of scholarly publishing The path forward requires reconciling our value for open science with the capability to pay for publishing in an open‐access journal The inherent value of open science should frame any open access decision